Relationship Between the Level of Maternal Education and Readiness for Caring for Low Birth Weight - Novi Indrayati; Dona Yanuar Agus Santoso; Muhammad Khabib Burhanuddin Iqomh (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
Low birth weight (LBW) has a birth weight of fewer than 2500 grams, is generally at high risk because, they are smaller than normal birth weight babies and immature organ function. LBW needs special care to prevent emergency conditions that can be life-threatening. A person's education level can be a factor in how a person's ability to receive information. This study aims to determine the relationship between a mother's education level and readiness to care for LBW. This study is a correlation study, using a cross-sectional design. The study population was mothers who had LBW who were treated in the perinatology room of the Kendal area hospital using accidental sampling techniques, the number of samples was 40 respondents. The research tool uses a questionnaire. The univariate analysis uses frequency distribution while bivariate analysis uses the spearmen test. The univariate analysis showed that the majority of mothers had a high school education level as much as 37.5%, 72.5% more than or 25 years, most of the parents were ready to care for LBW, namely 67.5%, while mothers who were not ready to care for LBW was 32.5%, the majority of mothers did not work as much as 57.5%. This Research shows that there is no relationship between the level of mother's education and the readiness to care for LBW with a P-value of 0.905. Mothers with higher education levels are not always ready to care for LBW.